Ab initio investigation of the affinity of novel bipyrazolate-based MOFs towards H2 and CO2. Issue 2 (7th November 2014) - Baima, J.; Macchieraldo, R.; Pettinari, C.; Casassa, S.
Abstract : Two recently synthesized bipyrazole-based metal organic frameworks were characterized and their different affinity toward small molecules was interpreted using ab initio simulations. Abstract : Two recently synthesized Zn and Cu tetramethyl-bipyrazole-based metal organic frameworks have been characterized and compared as regards their structural and electronic properties and their reactivity towards hydrogen and CO2 molecules. Ab initio calculations have been performed on periodic models with the B3LYP hybrid and an empirical long-range dispersion correction. Interactions with the probe molecules in the two structures are almost iso-energetic and in all cases the physisorption becomes reversible as the temperature increases. Topological analysis of the electron density has been used to fully characterize the chemical bonding. On the basis of our study, it can be inferred that the experimentally observed larger adsorption capacity of the Cu framework is not ascribable to the strong interaction of the guest molecules with an exposed metal ion but to the higher number of adsorption sites and to the larger void volume.